Spinal Deformity Surgery in Pediatric Patients With Cerebral Palsy: A National-Level Analysis of Inpatient and Postdischarge Outcomes. Issue 4 (May 2022) - Lee, Nathan J.; Fields, Michael; Boddapati, Venkat; Mathew, Justin; Hong, Daniel; Sardar, Zeeshan M.; Selber, Paulo R.; Roye, Benjamin; Vitale, Michael G.; Lenke, Lawrence G.
Study Design: Retrospective cohort. Objective: To provide a national-level assessment of the short-term outcomes after spinal deformity surgery in pediatric patients with cerebral palsy. Methods: A national, prospectively collected database was queried to identify pediatric (≤18 years) patients with cerebral palsy, who underwent spinal fusion surgery from 2012 to 2017. Separate multivariate analyses were performed for the primary outcomes of interest including extended length of stay (>75th percentile, >8 days), and readmissions within 90 days after the index admission. Results: A total of 2856 patients were reviewed. The mean age ± standard deviation was 12.8 ± 2.9 years, and 49.4% of patients were female. The majority of patients underwent a posterior spinal fusion (97.0%) involving ≥8 levels (79.9%) at a teaching hospital (96.6%). Top medical complications (24.5%) included acute respiratory failure requiring mechanical ventilation (11.4%), paralytic ileus (8.2%), and urinary tract infections (4.6%). Top surgical complications (40.7%) included blood transfusion (35.6%), wound complication (4.9%), and mechanical complication (2.7%). The hospital cost for patients with a length of hospital stay >8 days ($113 669) was nearly double than that of those with a shorter length of stay ($68 411). The 90-day readmission rate was 17.6% (mean days to readmission: 30.2). The most common reason for readmission included wound dehiscence (21.1%), surgical site infection (19.1%), other infection (18.9%), dehydration (16.9%), feeding issues (14.5%), and acute respiratory failure (13.1%). Notable independent predictors for 90-day readmissions included preexisting pulmonary disease (odds ratio [OR] 1.5), obesity (OR 3.4), cachexia (OR 27), nonteaching hospital (OR 3.5), inpatient return to operating room (OR 1.9), and length of stay >8 days (OR 1.5). Conclusions: Efforts focused on optimizing the perioperative pulmonary, hematological, and nutritional status as well as reducing wound complications appear to be the most important for improving clinical outcomes.